Impact of low-pressure pneumoperitoneum and local anesthetic combination on postoperative pain in patients undergoing laparoscopic cholecystectomy - Aydın, Oğuz Uğur; Soylu, Lütfi (The European Research Journal, 2018)
Objectives: Despite the advantages of laparoscopic cholecystectomy (LC), postoperative pain remains a major complaint for many patients. In this study, in patients undergoing LC, the application of LC via incisional bupivacaine and low inflation pressure, alone or combined, and a comparison of the effects on postoperative pain has been purposed.Methods: Patients were randomly assigned into the following 4 groups: the standard pressure (SP) group (n = 30); patients with an intraabdominal insufflation pressure of 12 mmHg, where bupivacaine application was not performed at the trocar locations. The SP+local anesthetic (LA) (SP+LA) group (n = 30); patients with an intraabdominal insufflation pressure of 12 mmHg, where bupivacaine application was performed at the trocar locations. The low pressure (LP) group (n = 30); patients with an intraabdominal insufflation pressure of 8 mmHg, where bupivacaine application was not performed at the trocar locations. The (LP+LA) group (n = 30); patients with an intraabdominal insufflation pressure of 8 mmHg, where bupivacaine application was performed at the trocar locations. Postoperative pain was evaluated using the visual analogous scale (VAS).Results: When the relationships between the VAS scores, gender, age, and American Society of Anesthesiologists classification were evaluated, no significant relationships between the groups were observed (p > 0.05). A significant relationship between the groups was detected with regards to the VAS scores, 1st analgesic application, 2nd analgesic application, and patients’ satisfaction (p < 0.05).Conclusions: The combination of low insufflation pressure with intrafacial preincisional local anesthetic infiltration in post-LC pain palliation is thought to be more effective and applicable.